Ἔθνη Θρᾳκῶν στὴ Θράκη τοῦ Αἰγαίου κατὰ τοὺς ἑλληνιστικοὺς καὶ ρωμαϊκοὺς χρόνους IΙ. Σαπαῖοι καὶ Σαπαϊκή - Παρισάκη Μαρία-Γαβριέλλα (Tekmeria, 2023)
Of two articles devoted to the Thracian tribes attested in Aegean Thrace during the Hellenistic and Roman periods, the second, published here, focuses on the tribe of the Sapaioi (the first, under the title «Ἔθνη Θρᾳκῶν στὴ Θράκη τοῦ Αἰγαίου κατὰ τοὺς ἑλληνιστικοὺς καὶ ρωμαϊκοὺς χρόνους, Ι. Κορπίλοι καὶ Κορπιλική», devoted to the Corpiloi, was published in Τεκμήρια 15 [2019-2020] 187-226). Once again, the relevant testimonia are mainly literary, spanning from the beginning of the fifth century BC (Xerxes’ march against Greece) to the second century AD (catalogue of strategiae of Thrace in Claudius Ptol- emy’s Geographika). But in this particular case, references to the Sapaioi also include a couple of inscriptions; among them, most prominently, the famous catalogue of the theorodokoi from Delphi and the equally renowned Sosthenes’ inscription from Paros. By gathering and analyzing these testimonia, the present article aims at defining more accurately the tribal territory of the Sapaioi and the limits of the Σαπαϊκὴ στρατηγία; at highlighting the intense and complex reality of a Thracian tribe in direct and close contact with the Greek and Roman worlds; and, finally, at stressing ‒through a brief and preliminary overview of the region’s archaeological map‒ the need for further archaeological research.